Life table of Delphastus pusillus (Coleoptera: Coccinellidae) on the whitefly Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - GARCÍA-GONZÁLEZ, JAVIER; BENÍTEZ-S., ÉDGAR RICARDO; LÓPEZ-ÁVILA, ARISTÓBULO (Revista Colombiana de Entomología, 2005)
The aim of this research was to construct the life table of the predator Delphastus pusillus (Le Conte) (Coleoptera: Coccinellidae), feeding on its prey, the greenhouse whitefly Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae). A group of 30 adults of known age were taken from among individuals reared in a colony maintained in the laboratory, and put into Petri dishes. Based on cohorts of 493 and 682 eggs of the predator, observations were made on the number of individuals alive at the beginning of each development stage, individuals that died in each stage, duration of each stage, female longevity, eggs laid per female, period of oviposition and sex ratio. The information collected was used to calculate the parameters of finite growth rate (  ), intrinsic rate of natural increase (rm), net reproductive rate (Ro), generation time (Tg), time to population doubling (Dt), time of female fecundity, oviposition rate, and the oviposition and survival curves of the predator. There was lower survival of D. pusillus in the early developmental stages, particularly the egg and larva1 stages. The estimated parameters obtained from the first and sixth generations were: Ro = 5.51 and 3.17, respectively, Dt = 23.0 and 20.5,  Lamda = 1.03 for both generations and rm = 0.03 for both generations. It is suggested that first generation female predators make a greater contribution to female daughters compared to the contribution made by females of the sixth generation maintained in laboratory.